NOMINATIVE POTENTIAL OF INTERJECTIONS AND RELATIVE CONSTRUCTIONS IN MAKING EXPLICIT AN EMOTIVE SITUATION - E. V. Yakovleva (Гуманитарные и юридические исследования)
The article studies general peculiarities of nominative potential as regards interjection and relative constructions in verbalizing and making explicit emotive situations in the process of production and perception of emotive texts. Multilayer hierarchy of sense in constructions under consideration, as well as their nominative potential can be realized according to certain "action schemes" with the reference to such constants as situational character, intentionality, modality and background knowledge. One of the key conditions to produce a highly performative effect by means of reference to subjective emotive, appealing and other relative constructions is the functional unity of formal text organization and the depicted emotive situation.